Turning Points and Fault Lines of Islamic Studies in Sweden - Janson, Torsten (Third Annual Swedish Middle East and North Africa Network (SWEMENA) Conference, Lund, Sweden, 2024-08-22 - 2024-08-23, 2024)
Roundtable presentation for: The Orient There and Back Again. Multidisciplinary Reflections on MENA Research and Sweden 1974-2024 (roundtable organised by Annika Rabo). Chair: Rouzbeh Parsi (Swedish Institute of International Affairs) Participants: Marianne Boqvist (Folke Bernadotte Academy), Torsten Janson (Lund University), Pernilla Myrne (University of Gothenburg), Annika Rabo (Stockholm University) and Karim Zakhour (Swedish Defence University)